2007
DOI: 10.1021/jf063498i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Structure of Phenolic Families as Hydroxycinnamic Acids and Catechins on Their Antioxidant Effectiveness in Minced Fish Muscle

Abstract: The antioxidant effectiveness of two different families of phenolic compounds, hydroxycinnamic acids and catechins, added as a power (0.001% w/w) to chilled minced horse mackerel muscle was evaluated. Caffeic acid, chlorogenic acid, o-coumaric acid, and ferulic acid were selected as hydroxycinnamic acids with similar molecular structures. Commercial catechins with different numbers of hydroxylic groups, including catechin, gallocatechin, catechin gallate, and gallocatechin gallate, were also tested. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 33 publications
11
96
0
Order By: Relevance
“…These results are in agreement with previously reported studies in which the capacity for donating electrons seems to play a more significant role in stabilizing the antioxidant efficiency of hydroxycinnamic acids than the ability for chelating metals 17 . The above results can be explained in terms of the structure: the morpholine NH + proton in 1-HCl can be easily transferred to interrupt the chain reactions of free radicals, which are responsible for lipid oxidation.…”
Section: Anti-oxidant Analysissupporting
confidence: 94%
“…These results are in agreement with previously reported studies in which the capacity for donating electrons seems to play a more significant role in stabilizing the antioxidant efficiency of hydroxycinnamic acids than the ability for chelating metals 17 . The above results can be explained in terms of the structure: the morpholine NH + proton in 1-HCl can be easily transferred to interrupt the chain reactions of free radicals, which are responsible for lipid oxidation.…”
Section: Anti-oxidant Analysissupporting
confidence: 94%
“…The result indicated that the extract could easily donate the electron to Fe (III) most effectively, thus reducing it to Fe (II). The reducing capacity measures the ease of the compounds in donating electrons (Medina et al 2007). Absolute ethanol (100 %) exhibited the similar capacity of extracting antioxidative compound with FRAP to water (P <0.05).…”
Section: Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 98%
“…Ferric reducing power assay is developed for direct test of total antioxidant power of compounds, measuring electron-donating ability (Benzie and Strain, 1999). According to Medina et al (2007), correlations between reducing power of hydroxycinnamic acids and rate of generation of TBARS, and peroxides during oxidation of minced mackerel muscle were -0.96 and -0.97, respectively. And they concluded that electron-donating ability seems to play an important role for antioxidant efficiency of phenolics.…”
Section: Reducing Powermentioning
confidence: 99%